Study on Coulomb explosions of ion mixtures. (22nd February 2016) - Boella, E.; Peiretti Paradisi, B.; D'Angola, A.; Silva, L. O.; Coppa, G.
Abstract : The paper presents a theoretical work on the dynamics of Coulomb explosion for spherical nanoplasmas composed by two different ion species. Particular attention has been dedicated to study the energy spectra of the ions with the larger charge-to-mass ratio. The connection between the formation of shock shells and the energy spread of the ions has been the object of a detailed analysis, showing that under particular conditions the width of the asymptotic energy spectrum tends to become very narrow, which leads to a multi-valued ion phase space. The conditions to generate a quasi-monoenergetic ion spectrum have been rigorously demonstrated and verified by numerical simulations using a technique that, exploiting the spherical symmetry of the problem, allows one to obtain very accurate and precise results.